The politics of criminal and juvenile justice policies in Japan - Chung, Jae Joon (Crime, law and social change, 2016)
Japanese adult criminal statistics of the execution of the jurisdiction are highly changeable or repeatedly fluctuate according to the characteristics of the regime. However, juvenile criminal statistics have been relatively stable because juvenile justice system is different from that of adult. The reason is that the criminal justice agencies, (i.e. public prosecutors and police officers), media reports, and victims’ activities directly impact on the adult criminal statistics. Furthermore public prosecutors have the right of prosecution and also have a broad discretion in the criminal justice system. On the contrary, the public prosecutors have no power to screen cases for prosecution in the juvenile justice system; that power resides with the family court judges. The family court judges are relatively more independent by the characteristics of the regime than the prosecutors. Juvenile justice is not a reaction against political issues, and juvenile criminal statistics are not a product of the regime’s characteristics. This article suggests new ideologies about juvenile justice policies to protect individual juveniles and to prevent crimes.